Effects of HIF-1α overexpression on mitochondrial function in aged mice with myocardial ischemia-reperfusion - ZOU,Tiantian (2022)
Abstract To evaluate the effects of HIF-1α overexpression on mitochondrial function in aged mice with myocardial ischemia-reperfusion (I/R). Mice were divided into 1) Blank (Sham) group; 2) Ischemia-reperfusion (I/R) group; 3) I/R+2ME2 group (I/R+HIF-1α blocker 2ME2. Compared with Sham group, in I/R group and I/R+2ME2 group, HR slowed down, LVDP and +dp/dtmax decreased, LVEDP, myocardial infarction area, and ROS generation rate was significantly increased; whereas the mitochondrial respiratory function (State3, RCR) and mitochondrial respiratory enzyme activity (NADH-OX, Cytc-OX and SUC-OX) were significantly reduced. Compared with the I/R group, the respiratory function of myocardial mtochondria (State3, RCR) and respiratory enzyme activity of myocardial (NADH-OX, Cytc-OX and SUC-OX) were significantly reduced in the I/R+2ME2 group; and the levels of p-HIF-1α and p-VEGF in the I/R+2ME2 group were significantly decreased. HIF-1α pathway upregulate the respiratory enzyme activity of myocardial and respiratory function of I/R myocardial mitochondria.